If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8x = 20 + 3(2 + -3x) 5 + -8x = 20 + (2 * 3 + -3x * 3) 5 + -8x = 20 + (6 + -9x) Combine like terms: 20 + 6 = 26 5 + -8x = 26 + -9x Solving 5 + -8x = 26 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 5 + -8x + 9x = 26 + -9x + 9x Combine like terms: -8x + 9x = 1x 5 + 1x = 26 + -9x + 9x Combine like terms: -9x + 9x = 0 5 + 1x = 26 + 0 5 + 1x = 26 Add '-5' to each side of the equation. 5 + -5 + 1x = 26 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 26 + -5 1x = 26 + -5 Combine like terms: 26 + -5 = 21 1x = 21 Divide each side by '1'. x = 21 Simplifying x = 21
| 9x^2+4y^2-36z=0 | | x^2+1.4x+13.95=0 | | -5(v+4)+31=5(3-v) | | -3(m+5)=2(m+5) | | 3(2x-5)=8x+9 | | 5000+0.8x=10000+0.5x | | 28=4y-2 | | 5ln(x+7)-7ln(x)=0 | | 18x(2x-x-28)=0 | | x=3+-0.5y | | 5x+12=x+29 | | -15=c+8 | | 2ln2x-1/2lnx | | (-6)2+-5= | | 6y^2-36y+x+55=0 | | (3*x)=24 | | Y/9=4/12 | | -x-5.2=12-2(x+0.6)-10 | | 2x+7=x+x+1 | | -(-3w-v)-4(-6v+w)= | | 6p+q-4p+14q= | | -4/3y-1=5/3y+7/6 | | -1/3y-1=5/3y+7/6 | | 0.2x+0.3=2.1 | | 7u+4=1+8u | | 5(a-2)=4(a-3) | | 5x+5=9x-9 | | 2t-(-4t-2)=14 | | 66x/67*53/33 | | f(x)=3x^2-6x+12 | | (15-4*3)*5-9= | | x^2+2xy+12=0 |